Dynamic economic dispatch feasible and optimal solutions. - Han, X.S (IEEE Transactions on power systems)
Dynamic economic dispatch is an extension of the conventional economic dispatch problem that takes into consideration the limits on the ramp rate of the generating units. This paper examines the factors that affect the feasibility and optimality of solutions to this problem. It proposes two new solution methods. The first is guaranteed to find a feasible solution even when the load profile is nonmonotonic. The second is an efficient technique for funding the optimal solution. The results obtained with these methods are compared with those obtained using previously published methods